1999
DOI: 10.1103/physrevb.59.6047
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic impurity scattering effects onTcandHc2inet al.

Abstract: We have studied the impurity effects on the superconducting transition temperature T c and the upper critical field H c2 in electron irradiated YBa 2 Cu 3 O y with in-plane oxygen defects and YBa 2 (Cu 1Ϫx Zn x ) 3 O y . It is found that the effects of the same type of defects or impurities on T c are the same regardless of the oxygen contents of the samples. Furthermore, T c decreases slower in irradiated YBa 2 Cu 3 O y than in YBa 2 (Cu 1Ϫx Zn x ) 3 O y . This may be well explained by the model that the scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 30 publications
1
32
1
Order By: Relevance
“…Evaluation of the critical temperature 13 and the upper critical field 15,16 dependences on the scattering rate showed their robustness to impurity scattering in the d-wave channel and led to a quantitative agreement with the experimental data. A strong support to these early theoretical predictions is provided by a recent experiment 17 with the electron irradiation created oxygen defects in Y-123 which confirms the extended nature of the scattering centers and the ability of the model to account for both the T c and H c 2 suppression by the disorder. Despite its preliminary success this approach neglects the magnetic scattering processes which however should be present at least for Zn and Ni impurity substitutions.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Evaluation of the critical temperature 13 and the upper critical field 15,16 dependences on the scattering rate showed their robustness to impurity scattering in the d-wave channel and led to a quantitative agreement with the experimental data. A strong support to these early theoretical predictions is provided by a recent experiment 17 with the electron irradiation created oxygen defects in Y-123 which confirms the extended nature of the scattering centers and the ability of the model to account for both the T c and H c 2 suppression by the disorder. Despite its preliminary success this approach neglects the magnetic scattering processes which however should be present at least for Zn and Ni impurity substitutions.…”
supporting
confidence: 67%
“…So far, an application of the nonmagnetic scattering expression for the reduced H c 2 slope 15,16 in the interpretation of the critical field of the electron irradiated Y-123 has confirmed the anisotropy parameters of the model determined from T c suppression in this compound. 17 The orthorhombic distortion of the crystal lattice in the Y-123 superconductor leads to the (dϩs)-wave superconductivity in this compound. 36 The photoemission, tunneling, and thermodynamic measurements put an upper bound of ϳ10% on the relative size of the s-wave component in the (dϩs)-wave superconducting state.…”
Section: ͑8͒mentioning
confidence: 99%
“…It has been shown that when the scattering is close to being in phase it reproduces the observed T c suppression [11,12] and the H c2 critical field initial slope [8,13] or f (k) = sgn (k x k y ) it gives ef = 0 and strong suppression of the critical temperature. The differing effect of these two groups of impurity potential is also seen in the solution to the gap equation.…”
Section: Critical Temperature and Order Parameter Suppressionmentioning
confidence: 73%
“…In addition to a possible identification of the superconducting state, this experiment may shed light on the nature of the quasiparticle scattering process -issue, which is important to the interpretation of the impurity pair-breaking effect in the d-wave superconductor. It has been shown that the weak impurity-induced suppression of the critical temperature, which is unexpected for d-wave superconductivity [5,6,7,8] can be understood assuming a momentum-dependent (anisotropic) impurity potential [9,10,11,12]. In the present paper we discuss the effect of anisotropic impurity scattering on the critical temperature, local density of states in the vicinity of a single impurity, and the quasiparticle density of states for a finite impurity concentration in a d-wave superconductor.…”
Section: Introductionmentioning
confidence: 99%
“…Although the main feature of the four-fold symmetry of the tunneling currents is captured by the model of isotropic impurity scattering the observed spatial dependence of the quasiparticle density of states is far more complex, and may originate from a non trivial structure of the impurity potential. This aspect of the quasiparticle scattering process has been raised in the discussion of macroscopic measurements in these compounds [8,9,10,11]. It has been shown that the unexpected for the d-wave superconductivity weak impurity-induced suppression of the critical temperature can be understood within a scenario of a momentum-dependent (anisotropic) impurity scattering potential [12,13,14,15].…”
mentioning
confidence: 99%